Metabolomic and microbiota profiles in cervicovaginal lavage fluid of women with high-risk human papillomavirus infection - Su Shen; Shixian Zhao; Jinjun Shan; Qingling Ren (Scientific Reports)
Abstract The presence of high-risk human papillomavirus (HR-HPV) contributes to the development of cervical lesions and cervical cancer. Recent studies suggest that an imbalance in the cervicovaginal microbiota might be a factor in the persistence of HR-HPV infections. In this study, we collected 156 cervicovaginal fluid (CVF) of women with HR-HPV infection, which were divided into three groups (negative for intraepithelial lesions = 78, low/high-grade squamous intraepithelial lesions = 52/26). We performed metabolomics and 16 S rRNA sequencing to identify changes in metabolites and cervicovaginal microbiota among patients with HR-HPV infection and varying grades of cervical lesions. We detected 164 metabolites and 389 flora types in the three groups. Ten CVF metabolites—N-methylalanine, phenylacetaldehyde, succinic acid, 2-3-dihydroxypyridine, DL-p-hydroxylphenyllactic acid, gluconic acid lactone, guanine, glucose-6-phosphate, erythrose, and sucrose showed significant associations with disease severity and distinct separation patterns in HR-HPV-infected patients with LSIL and HSIL, with an area under the curve of 0.928. The most abundant microbial communities in the CVF were Gardnerella. Gardnerella was found to be associated with increased levels of succinic acid, thereby highlighting distinct metabolic profiles. These findings suggest that the development of cervical lesions resulting from persistent HR-HPV infection is associated with significant alterations in systemic metabolism and shifts in the cervicovaginal microbiota, providing valuable insights into the metabolic and microbiota changes linked to disease severity.